The expression of CD177 and it`s relation to serum soluble transferrin receptors (sTfR-1) in β thalassemia patients - Saja Lateef Alkafaji; Jaffar Nouri Jaffar Alalsaidissa (Iraqi Journal of Cancer and Medical Genetics, 2019)
Background: Ineffective erythropoiesis has a well-known role in the pathophysiology of β-thalassemia syndromes. CD177 expressionwas studied in diverse hematological, clinical, and immunological disorders (like myeloproliferative neoplasms MPN,transfusion-related acute lung injury TRALI; neonatal alloimmune neutropenia).Aims of the Study:1. To assess significance of CD 177 as a marker of increased erythropoietic activity in patients with β thalassemia major andminor.2. to correlate CD177 expression with serum transferrin receptors (sTfR -1) and absolute neutrophils count.Patients and Methods: this cross sectional study performed on 25 patients with β thalassemia major, 25 patients with β thalassemiaminor, along with 25 healthy control, all were selected from Babylon Maternity and Children Teaching Hospital,Investigations included complete blood counts, hemoglobin analysis (by high performance liquid chromatography HPLC ,CRP,ESR, serum ferritin, flowcytometric immunophenotyping for CD177 expression and percentage, mean fluorescence intensity(MFI) expression on gated neutrophil and serum sTfR-1 levels were measured by enzyme immunoassay.Results: The mean expression of CD177% was higher in β thalassemia major than minor and control, but it did not reach levelof significance (p=0.22).CD177 Mean fluorescence intensity (MFI )had no significant difference (p=0.74) among β thalassemia major , minor and control.Mean levels of sTfR-1 in thalassemia major, minor and control group were significantly differing (p<0.0001).Within β thalassemia major, there was a negative significant correlation between Hb level and serum transferrin receptor-1 concentration(p=0.007), ` a significant positive correlation between serum ferritin and sTfR-1(p=0.03).Conclusions: CD177 expression (percentage and MFI) as a marker of erythropoietic activity was insignificantly elevated in βthalassemia patients ,while sTfR-1 levels showed statistically significant difference in relation with erythropoietic activityin thalassemiapatients.